Derivative free Levenberg-Marquardt method for solving fuzzy nonlinear equation - A.U., Omesa; I. M., Sulaiman; M., Mamat; M.Y., Waziri; A., Shadi; M.A., Zaini; Kalfin, .; I., Sumiati (2021)
In this paper, we present a derivative-free computational method for solving fuzzy nonlinear equation. Derivative-free technique avoids computing the derivative by generating an estimate to the derivative. This is made possible by inserting the estimate of F'(xk) in Levenberg-Marquardt’s method. Numerical experiments are carried out which shows that, the method is efficient.